The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0100-72032012000200006
|View full text |Cite
|
Sign up to set email alerts
|

Resistência à insulina em mulheres com síndrome dos ovários policísticos: relação com as variáveis antropométricas e bioquímicas

Abstract: The prevalence of insulin resistance varied according to the method used, and it was greater the higher the body mass index. Lipid accumulation product was also related to insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
(49 reference statements)
1
3
0
8
Order By: Relevance
“…Similar results were found in studies conducted in other countries, in which LAP was a better marker of glucose imbalance and a stronger predictor of DM than BMI. 13 - 20 The present study confirms that LAP is sensitive to identify dysfunctions related to glucose metabolism, even after adjustment for drug use and multiple confounders.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results were found in studies conducted in other countries, in which LAP was a better marker of glucose imbalance and a stronger predictor of DM than BMI. 13 - 20 The present study confirms that LAP is sensitive to identify dysfunctions related to glucose metabolism, even after adjustment for drug use and multiple confounders.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies based in LAP confirmed its association with classical risk factors for CVD. 17 - 20 Therefore, the aim of this study was to extend current knowledge of LAP, by evaluating the impact of this parameter on LDL and HDL size, considering the potential influence of confounders.…”
Section: Introductionmentioning
confidence: 99%
“…Trata-se de um modelo matemático desenvolvido em 1985, o qual reduz a sensibilidade à insulina pela simples medida da glicemia e insulina séricas de jejum, e tem sido um dos principais métodos para avaliar a resistência insulí-nica pela sua fácil aplicação e boa correlação com técnicas diretas de avaliação da resistência a insulina (MATTHEWS et al, 1985;SOUZA;LIMA, 2005;VASQUES et al, 2008;MATOS;GIORELLI;DIAS, 2011;PONTES et al, 2012). Em 1998, o índice HOMA1-IR foi atualizado com alguns ajustes fisiológicos para uso em um programa computacional, sendo então denominado HOMA2-IR (LEVY; MATTHEWS; HERMANS, 1998).…”
Section: Introductionunclassified
“…A obesidade é um achado frequente nestas pacientes, presente em 40 a 60% delas. O diagnóstico oportuno e a correta intervenção nos casos de SOP, faz-se importante uma vez que esta síndrome está relacionada ao aumento de risco de resistência insulínica, intolerância à glicose, diabetes mellitus tipo 2, doença cardiovascular e síndrome metabólica observadas também nas adolescentes com SOP [6][7][8] .…”
Section: Introductionunclassified